Pengaruh Kualitas Pelayanan Dan Kualitas Produk Terhadap Loyalitas Pelanggan Pada Konveksi Hijab CV.ZAM-ZAM Candimulyo Jombang - Muhammad Fadhli Robby Mukhtarom; Lilis Sugi Rahayu Ningsih (CV. ALIM'SPUBLISHING, 2023)
Costumers’ have their own taste to buy something at somplace, beside when they found a product or a place that suits to their taste arises a desire to become customer that loyal to that product or a place . Object of this research is hijab convection CV.ZAM-ZAM Candimulyo Jombang. Purpose of this reseacrh is to know the effect of service quality and product quality on customer loyalty at hijab convection CV.ZA-ZAM Candimulyo Jombang This resecarh methode is kuantitative . The populations are customersrs who buy or booking at the hijab cnvection CV.ZAM-ZAM Candimulyo Jombang wich around 150 customers in a month with 30 respondens. Data analysised by statistic test helped by SPSS25. The results showed that factors that 1) the service quality has a partial effect on customer loyalty with value of 2.125 on partial test. 2) the product quality has a partial effect on customer loyalty with value of 2.993 on partial tes. 3) the service quality and product quality has a simultaneous effect on customer loyalty with value of 11.938 on simultaneous test.